2018
DOI: 10.1080/09524622.2018.1538902
|View full text |Cite
|
Sign up to set email alerts
|

Crowd intelligence can discern between repertoires of killer whale ecotypes

Abstract: Call classifications by human observers are often subjective yet they are critical to studies of animal communication, because only the categories that are relevant for the animals themselves actually make sense in terms of correlation to the context. In this paper we test whether independent observers can correctly detect differences and similarities in killer whale repertoires. We used repertoires with different a priori levels of similarity: from different ecotypes, from different oceans, from different pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Danishevskaya et al (2020) found that human observers distinguished Icelandic and Norwegian killer whale calls but clustered them with those of North Pacific residents. To date only one study indicates a link between Icelandic and Norwegian killer whale call repertoires: Strager (1995) found two matches between call types recorded off Norway and those recorded off East Iceland by Moore et al (1988).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Danishevskaya et al (2020) found that human observers distinguished Icelandic and Norwegian killer whale calls but clustered them with those of North Pacific residents. To date only one study indicates a link between Icelandic and Norwegian killer whale call repertoires: Strager (1995) found two matches between call types recorded off Norway and those recorded off East Iceland by Moore et al (1988).…”
Section: Discussionmentioning
confidence: 99%
“…However, the most recent photographic data sets collected in both Iceland and Norway have not been compared yet and this ongoing work might shed light on the present-day connectivity between these populations. Danishevskaya et al (2020) found that human observers distinguished Icelandic and Norwegian killer whale calls but clustered them with those of North Pacific residents. To date only one study indicates a link between Icelandic and Norwegian killer whale call repertoires: Strager (1995) found two matches between call types recorded off Norway and those recorded off East Iceland by Moore et al (1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different killer whale populations produce unique repeated pulsed calls, called “discrete” or “stereotyped” calls 27 , 33 , 34 , 37 , 38 . Discrete calls can be reliably distinguished aurally and visually on a spectrogram and used to differentiate among populations 37 , 39 42 . Transient killer whale calls are also often characterized by an audible quavering of the fundamental sound frequencies and fewer call syllables 40 , 43 .…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of crowd intelligence can be observed in our daily lives as the proverb goes "two heads are better than one" and "everybody's business is nobody's business" (Danishevskaya et al, 2018). Especially, with the rapid development of the network technology, crowd intelligence becomes more complicated and universal, as human, enterprises, governments, equipment and articles become increasingly intelligent, and these intelligent agents to connect each other to form numerous crowd network systems, such as e-commerce platforms, networked supply chains, Wikipedia and network elections (Bonney et al, 2009).…”
Section: Introductionmentioning
confidence: 99%